THE EFFECT OF COMPANY FINANCIAL PERFORMANCE ON CAPITAL STRUCTURE (CASE STUDY ON FINANCING COMPANIES ON BEI PERIOD 2015-2020) - Dinar Sukma Tantra; Dini Hariyanti (Jurnal Ekonomi, 2023)
The objective of this research is to analyze and examine the impact of company's financial performance towards capital structure in financial companies in Indonesia for the 2015-2020 period. In this research, the data are from the Indonesia Stock Exchange (BEI), Financial Services Authority (OJK), and financial report of each company. Capital structure is measured using the Debt to Equity Ratio (DER) variable. Otherwise Financial Performance can be measured by Financing to Asset Ratio (FAR), Non Performing Loan (NPL), Price Earning Ratio (PER), Return on Assets (ROA), Return on Equity (ROE) variables. This research is using seven samples of financial companies in Indonesia for the 2015-2020 period in each semester. The researcher is using quantitative with seven sample financial companies listed on BEI & method with the research performance measured by the panel data regression. The results from panel data regression show that the fixed effect model is suitable and chosen. From this research explains that Financing to Asset Ratio (FAR) & Price Earning Ratio (PER) variables have shown positive impact towards capital structure variables, whereas Non Performing Loans (NPL), Return on Assets (ROA), Return on Equity (ROE) Have shown negative impact towards capital structure. The research is expected to be able to overview the capital structure for the company and concerns regarding the cash flow. The next research is expected to be able to add research variables and the year of the research for more perfection.